Local governance: a model of sustainable rural resource management for the Third World. (1st January 2000) - Barkin, David
Global integration is creating opportunities for new strategies for rural development that revalue the contribution of traditional production strategies. These new strategies involve the redevelopment of peasant communities, carving out political spaces to allow them to exercise their autonomy, and defining ways in which their organisations will guide production for themselves and for commerce with the rest of the society. This approach offers succour to rural communities, by providing a means to diversify production that offers an opportunity for the society to confront the challenges of environmental management and conservation in an active and meaningful way, with a group of people uniquely qualified for such activities.